Global burden and trend of tuberculosis in children and adolescents (under 15 years old) from 1990 to 2021, with projections to 2040 - Yuanhao Liang; Jiayi Wang; Jianzhou Yang; Jinjia Liu; Xiaofeng He (Frontiers in Public Health, 2025)
BackgroundTuberculosis (TB) remains a significant global health issue, but its burden among children and adolescents under 15 years old is not well quantified. This study evaluates TB trends in this age group from 1990 to 2021 and projects future trends through 2040.MethodsWe used data from the Global Burden of Disease Study (GBD) 2021 to assess the incidence and mortality of TB in children and adolescents (under 15) from 1990 to 2021. A Bayesian age-period-cohort model was employed to project the TB burden.ResultsIn 2021, there were 799,047 new TB cases and 81,870 TB-related deaths among children, with an age-standardized incidence rate (ASIR) of 40.01 per 100,000 population and an age-standardized mortality rate (ASMR) of 4.16 per 100,000 population. From 1990 to 2021, the ASIR declined by 2.4% annually, while ASMR decreased by 4.19% per year. However, drug-resistant TB, especially extensively drug-resistant TB, increased significantly. The burden was highest in low-SDI regions, particularly among children under 5, who accounted for over 75% of TB-related deaths. Projections to 2040 indicate continued declines in ASIR and ASMR for all TB forms, including drug-resistant and TB-HIV co-infections.ConclusionSustained investment in TB control programs, particularly in low-SDI regions, is crucial. Addressing drug-resistant TB and TB-HIV co-infection should be prioritized in global public health strategies.